How Volunteers Contribute to Persons with Dementia Coping in Everyday Life - Malmedal,Wenche; Steinsheim,Gunn; Nordtug,Bente; Blindheim,Kari; Alnes,Rigmor; Moe,Aud (Journal of Multidisciplinary Healthcare, 2020)
Wenche Malmedal,1,2 Gunn Steinsheim,1,3 Bente Nordtug,4 Kari Blindheim,2,5 Rigmor Einang Alnes,5 Aud Moe2,4 1Department of Public Health and Nursing, Norwegian University of Science and Technology (NTNU), Trondheim, Norway; 2Centre of Care Research, Steinkjer, Norway; 3Centre for Development of Institutional and Home Care Services Trøndelag County, Åfjord, Norway; 4Faculty of Health Science, Nord University, Bodø, Norway; 5Department of Health Sciences Ålesund, Norwegian University of Science and Technology (NTNU), Ålesund, NorwayCorrespondence: Wenche MalmedalDepartment of Public Health and Nursing, Norwegian University of Science and Technology (NTNU), Trondheim 7491, NorwayTel +47 97642156Email wenche.k.malmedal@ntnu.noIntroduction: The society needs volunteers to fulfill its duty to ensure that people with dementia have active and meaningful everyday lives. Volunteers seem to experience their work as positive and meaningful for their own part, but we know less about what motivates volunteers to start working in home-dwelling dementia care and what motivates them to continue their engagement. This study seeks to close some of the knowledge gaps that exist regarding volunteers’ engagement in activities for persons with dementia.Aim: The aim of this study was to explore what motivates volunteers to start engaging in volunteer work in home-dwelling dementia care and what motivates them to continue their engagement.Methods: The study design was qualitative, using focus group interviews. Three focus group interviews (n=16) took place between May and June 2018. The text was analyzed using content analysis.Results: Findings in this study indicate that the volunteers were motivated by the feeling of doing an important job for the persons with dementia and their relatives, and that they contribute to their coping with everyday life. Other motivating factors included feeling important to someone, gaining friendship, and sharing common interests. They also believed that they do an important job for the community to ...